Whiskerella - Vernon, Ursula (Vernon, Ursula. Hamster princess, 2018)
"When a fairy godmouse forces Whiskerella to wear glass slippers and attend balls night after night in search of a happily ever after, it's up to Princess Harriet Hamsterbone to break the spell and save the day"--